The Influence Of The Think Talk And Write (Ttw) Learning Model On Students' Learning Outcomes In The Subject Of Academic Morals In Madrasah - Zaman, Nurul (Yayasan Marwah Madani Riau, 2025)
The purpose of this research is to find out whether there is an effect of the Think Talk and Write learning model on student learning outcomes in the subject of Islamic cultural history in class VIII MTs Nurul Yaqin Pekanbaru. This research method uses quantitative methods with data collection techniques in the form of observation, testing and documentation. The number of samples in this study were two classes of class VIII students consisting of 45 students. The data analysis technique used is Validity Test, Reliability Test and Normality. Based on the results of this study, from the results of observations at five meetings, the percentage value of the research results can be calculated to get the average value. After adding up all five meetings, the percentage results are 80% and it can be concluded that the Think Talk and Write (TTW) learning model is categorized as Good. While the test results from the Wilcoxon test with Asymp.Sig (2-tailed) is 0.000. Because 0.000 is smaller than 0.05, it is concluded that Ho is rejected and H1 is accepted. This means that there is a difference between the learning outcomes of Aqidah Akhlak for the pretest and posttest. So it can be concluded that there is an effect of using the Think Talk and Write learning model on the learning outcomes of Aqidah Akhlak students in class VIII MTs Nurul Yaqin Pekanbaru. The results of this study indicate that the implementation of the Think Talk and Write (TTW) learning model has a positive impact on improving student learning outcomes in the subject of Academic Morals for class VIII MTs Nurul Yaqin Pekanbaru. The TTW model encourages students to think critically, interact through discussions, and express their understanding in written form, so that the learning process becomes more active and meaningful. The practical implication is that teachers can use the TTW model as an alternative effective learning strategy to instill academic moral values ​​more deeply, while for students this model helps shape responsible, communicative, and reflective academic attitudes.